Organizational Ethos: Empact on Work Performance of Employees - Adhikari, Narayan Prasad; Budhathoki, Jhupa Kumari (Cognition, 2024)
The objective of this study is to explore how organizational ethos affects employees' work performance. This study is based on meta-analysis research design and the literature review. Organizational principles, practices, and distinctive features of culture all contribute to the dimension of corporate culture. The foundational element of an organization's ethos is its value system. The corporate ethos fosters professionalism among the employees. Workplace performance was found to be positively impacted by four organizational ethos sub-elements: managing change, attaining goals, coordinating teamwork, and cultural strength. Organizational ethos has a significant impact on the operations, personnel, and productivity of a wide range of services. This study demonstrates that if employees are dedicated and has the same values as their organizations; their performance in attaining organizational objectives will be achieved. To enhance the overall performance of the workforce and the services, managers and executives are encouraged to foster a strong organizational ethos. The study's findings show that organizational ethos has a major impact on employee motivation, develops personal growth, influences communication, and enhances organizational values, group decision-making, and conflict resolution.